Color Blind Test Using Ishihara Method for Mercu Buana University Prospective Students Selection - Asri, Sri Dianing; Darmawan, Adhitya Dwiki; Wibowo, Novianti Putri; Wibowo, Dimas Riyanto (LPPM Universitas Islam 45 Bekasi, 2021)
Mercu Buana University is a private university which consists of seven faculties. At the Faculty of Design and Creative Arts, Faculty of Communication Sciences and Faculty of Engineering, additional requirements are required for new student candidates, i.e. a color blindness free certificate. Color blindness is a vision disorder caused by the inability of the eye cone cells to perceive a certain spectrum of colors. There are many ways to test someone's color blindness, one of which is by using the Ishihara method. To obtain a color blindness free certificate, prospective students must visit a clinic or hospital, carry out the applicable color blind test procedure, then bring the results to campus. Based on these problems, the research was conducted with the aim of making a color blind test application that can issue a recommendation letter based on the test results of prospective new students. The system development method uses System Development Life Cycle. The results of the study were an android-based color blind test application that was able to detect color blindness using the Ishihara method and issued a recommendation letter based on the test results of prospective new students in the on-time application.